Histopathological study of distal colonic polyps - Shyshkin, M. A.; Шишкін, Максим Андрійович (My University, 2020)
Сolorectal polyps are neoplasms which are revealed during colonoscopy procedure most commonly. Clinical significance of the polyps caused by their malignant potential, since it is known that 60-70% colorectal adenocarcinoma cases are preceded by benign polyp. Nowadays, all colonic polyps are basically divided into two groups - serrated and adenomatous polyps. Serrated polyps are distinguished by their saw-toothed histological appearance. This group includes hyperplastic polyps with relatively low malignant potential as well as traditional serrated adenomas and sessile serrated adenomas that have high malignant potential. The group of adenomatous polyps is characterized by typical gland-like histological appearance. Based on features of the gland structures the second group is subdivided into tubular, villous, and tubulovillous adenomas. The risk of malignization significantly increases in the named sequence.